2022
DOI: 10.3390/nu14091849
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Status Is Associated with Increased Risk of Mortality in Korean Men and Adults with Hypertension: A Population-Based Cohort Study

Abstract: Background Recent randomized controlled trials (RCTs) have shown no effect of vitamin D supplementation on cardiovascular disease, cancer events and mortality or all-cause mortality in Western populations. However, there has been a lack of research on populations with low vitamin D status, including Asians. In addition, there have been indications that an individual’s sex or hypertension status may affect the relationship between vitamin D status and mortality. In this study, we retrospectively assessed the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al reported that serum 25(OH)D concentrations were linearly and negatively linked with the risk of mortality from all causes (p = 0.012) and from CVD (p = 0.010) among individuals with hypertension in the US based on the 2001–2004 NHANES with mortality data available through 2006 [ 9 ]. Results from the KNHANES also showed that among individuals with hypertension, those with low serum 25(OH)D status had a higher risk of cardiovascular and all-cause death [ 10 ]. Unlike hypertension, the adverse consequences of prehypertension have not received sufficient attention.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al analyzed data from the US NHANES and found that serum 25(OH)D were linearly and inversely associated with the risk of mortality from all causes (HR:0.97, 95%CI 0.95–0.99) and from CVD (HR:0.95, 95%CI 0.91–0.99) after adjustment for age, sex, ethnicity, education, body mass index (BMI), smoking status, drinking status, physical activity, vitamin supplement use, serum lipids, and history of CVD [ 9 ]. Based on the Korean National Health and Nutrition Examination Survey (KNHANES), Park et al found that serum 25(OH)D below 20 ng/mL is associated with a higher risk of mortality in Korean adults with hypertension after adjusting for age, sex, region, income, smoking status, alcohol consumption, physical activity, and BMI [ 10 ]. However, long-term effects of serum 25(OH)D on the risk of death from all causes and CVD are less well understood in individuals with prehypertension.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 According to the findings from observational studies and clinical trials assessing the effect of vitamin D supplements on CVDs, there are still contradictory results. [17][18][19][20][21] Although meta-analysis studies have been conducted, cohort articles and clinical trials have not been considered together. Accordingly, this systematic review and meta-analysis aimed to update the effect of vitamin D supplements on CVDs considering cohort studies and clinical trials.…”
mentioning
confidence: 99%